CHALLENGES WHEN DEVELOPING PERFORMANCE INDICATORS - Brindusa Maria POPA (Journal of Defense Resources Management, 2015)
Abstract Developing key performance indicators (KPIs) represents one step closer to the achievement of objectives and strategic vision of the organization. They are important elements of the pathway towards performance, they evaluate and indicate the level of progress, guide the organizational strategy, they can be considered even the qualitative or quantitative expression of the execution of the strategy. Building reliable and appropriate measurement systems is one of the most difficult stage in the performance evaluation process. Such systems of management will help the executives and the management teams identify and build upon the elements that create competitive advantage and opportunities for better results.